Enhancing Research Imapct: Rethinking Research Approach - Rai, Ajeet Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Educational Research is being criticised for a decline in its impact specifically in terms of use of the knowledge created by practitioners and in bringing about change at the ground level reality. The contemporary research culture promotes theoretical oriented research projects yielding knowledge that has a potential use in some future time. To overcome the problem a complimentary research approach is proposed that is embedded, engaged and emergent in nature involving collaboration and co-development of the researcher as well as the practitioner located in the Jeffersonian framework of research. The three significant perspectives underpinning the Three-E approach are elaborated and explained to provide the rationality of the approach proposed. The article is suggestive in nature rather than directive as the nascent stage of the ideas proposed and the research approach floated is fully acknowledged. Nevertheless, this article expects further deliberations on the issues raised and the ideas used to generate the complimentary research approach.